2018
DOI: 10.1002/acm2.12266
|View full text |Cite
|
Sign up to set email alerts
|

Does intensity modulation increase target dose calculation errors of conventional algorithms for lung SBRT?

Abstract: PurposeConventional dose algorithms (Type A and Type B) for lung SBRT can display considerable target dose errors compared to Type‐C algorithms. Intensity‐modulated techniques (IMRT/VMAT) are increasingly being utilized for lung SBRT. Therefore, our study aimed to assess whether intensity modulation increased target dose calculation errors by conventional algorithms over conformal techniques.MethodsTwenty lung SBRT patients were parallely planned with both IMRT and dynamic conformal arc (DCA) techniques using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
(90 reference statements)
0
2
0
Order By: Relevance
“…Another limitation is that a variety of dose algorithms were used for the retrospective cohort with varying levels of calculation accuracy especially in terms of heterogeneity corrections. Of them, Pinnacle CCC and Eclipse AAA are known to be more accurate than iPlan PBC, although our previous studies have found that the dose differences among the algorithms are mostly seen for the target especially at the target periphery and much less so for the OARs especially in the low dose regions [35]. Nevertheless, not accounting for the different dose algorithms could introduce additional uncertainty in our results.…”
Section: In the Appendix)mentioning
confidence: 79%
“…Another limitation is that a variety of dose algorithms were used for the retrospective cohort with varying levels of calculation accuracy especially in terms of heterogeneity corrections. Of them, Pinnacle CCC and Eclipse AAA are known to be more accurate than iPlan PBC, although our previous studies have found that the dose differences among the algorithms are mostly seen for the target especially at the target periphery and much less so for the OARs especially in the low dose regions [35]. Nevertheless, not accounting for the different dose algorithms could introduce additional uncertainty in our results.…”
Section: In the Appendix)mentioning
confidence: 79%
“…Therefore, the dose calculation results of kV-CBCT in this study are reliable. For MV beams, several studies 26,27 confirmed that there was no significant difference between the lung dose distribution calculated by CCC algorithm and that simulated by MC code.…”
Section: Discussionmentioning
confidence: 93%